Addition of a protease to low crude protein density diets of broiler chickens. Issue 1 (1st January 2018) - Mohammadigheisar, Mohsen; Kim, In Ho
ABSTRACT: A total of 864 1-day-old Ross 308 broiler chickens with an average body weight of 40 ± 1.1 g were used to determine the effect of adding protease to broiler chickens diets with different crude protein (CP) density on growth performance, carcase characteristics, excreta microbiota, blood constituents, and nutrient digestibility. The chicks were allotted in pens with 18 birds/pen and 12 pen/treatment. Treatments were T1: basal diet, T2: T1 − 1.0% CP, T3: T2 + 0.05% protease, T4: T2 + 0.1% protease. Results showed that supplementing low CP diets with protease alleviated the negative effects of lowering dietary CP on BWG and FCR ( P < .05) on days 1–21. Addition of protease to low CP diets improved BWG on days 1–35 ( P < .05). Feeding the chickens with low CP diet reduced ( P < .05) digestibility of dry matter (DM), but the addition of protease improved digestibility of DM. The results showed that lowering dietary CP had detrimental influence ( P < .05) on digestibility of total essential amino acids (TEAA) and total non-essential amino acids (TNEAA). It is concluded that reduction of dietary CP had a negative effect on broiler chickens and the addition of protease alleviated the negative effects and improved chickens performance.